Analisis Strategi Penetapan Harga Jual Kelapa Sawit Pada Pt Parna Agro Mas Sekadau Kalimantan Barat - Novita, Sri (Jurnal Ekonomi STIEP ( JES ), 2019)
Oil palm plantations are one of the plantations crops in Indonesia who has a pretty bright future. The areaof oil palm plantations in Indonesia is expanding so that later established a modern palm oil processing factoryand oil palm research centers.The purpose of this study is to find out the strategy that is done inside set the selling price of palm oil, findout the constraints in setting the selling price and to find out the policies of the company in determining the sellingprice of palm oil to PT Parna Agro Mas Sekadau West Kalimantan.The method of research conducted is by using data and data sources obtained directly from PT Parna AgroMas Sekadau West Kalimantan in the form of data on the production and sale of palm oil from 2015 to 2017.The result showed that the company doesn’t just set one price, but a price structure which reflectsgeographical diversity and costs, market segment demands, purchase time, order level, and other factors. The priceadjustment strategy carried out is : (1) geographical pricing, (2) (price discount and allowances, (3) promotionalpricing, (4) discriminatory pricing.